Efficacy of dacomitinib in patients with EGFR‐mutated NSCLC and brain metastases. Issue 24 (9th November 2021) - Zhang, Jinyao; Wang, Yan; Liu, Ziling; Wang, Lin; Yao, Yu; Liu, Yutao; Hao, Xue Zhi; Wang, Jianyang; Xing, Puyuan; Li, Junling
Abstract: Background: Dacomitinib is a second‐generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) which is superior to first‐generation EGFR TKI in ARCHER 1050. However, the activity of dacomitinib in the central nervous system (CNS) is not known as ARCHER 1050 did not include patients with baseline brain metastases. This study aimed to describe dacomitinib's activity in the CNS in a real‐world setting. Patients and Methods: Thirty‐two patients who were receiving dacomitinib for advanced non‐small‐cell lung cancer (NSCLC) with EGFR mutations and brain metastasis were included in this study. Patients who received prior EGFR TKIs were excluded from this trial. Case report forms were collected to determine treatment outcomes. Results: Among 32 patients with EGFR‐mutated NSCLC and brain disease, eight were included in the CNS evaluable for response group. The intracranial objective response rate (iORR) was 87.5% (95% confidence interval [CI] 47.3–99.7%) and the intracranial disease control rate (iDCR) was 100% (95% CI 63.1–100%). In 30 evaluable patients with measurable or nonmeasurable brain lesions, the iORR was 66.7% (95% CI 47.2–82.7%) and the iDCR was 100% (95% CI 88.4–100%). Median intracranial duration of response (iDoR) and intracranial progression‐free survival (iPFS) were not reached, with a one‐year iDoR rate of 72.2% (95% CI 48.7–95.7%) and a 1‐year iPFS rate of 71.2% (95% CI 51.0–91.4%), respectively. The majority of patients experienced low‐grade (G1/2) toxicities, which are reversible. Conclusion: This study suggests that dacomitinib demonstrated CNS efficacy in patients with EGFR TKI‐naïve EGFR‐mutated NSCLC in the real‐world setting. The safety profile was tolerable and manageable. Abstract : This study is the largest multicentric trial to demonstrate the efficacy of dacomitinib in NSCLC patients with EGFR mutation and brain metastases. The survival time of NSCLC patients with EGFR mutation and brain metastases could be prolonged with dacomitinib treatment.